2012
DOI: 10.1021/co2001789
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage Materials Discovery via High Throughput Ball Milling and Gas Sorption

Abstract: The lack of a high capacity hydrogen storage material is a major barrier to the implementation of the hydrogen economy. To accelerate discovery of such materials, we have developed a high-throughput workflow for screening of hydrogen storage materials in which candidate materials are synthesized and characterized via highly parallel ball mills and volumetric gas sorption instruments, respectively. The workflow was used to identify mixed imides with significantly enhanced absorption rates relative to Li2Mg(NH)2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…As a result instrument manufacturers are attempting to develop automated high throughput gas adsorption analyzing units. One notable example of which is a volumetric technique that can analyze 28 samples in parallel recently developed by Wildcat Discovery Technology Inc. [ 28 ] This apparatus has recently been demonstrated in a high throughput study of cation exchanged forms of zeolites Na-A (LTA) and Na-X (FAU) for use in CCS, with the results acquired from the high throughput analyzer validated against data acquired from a conventional Micromeritics ASAP 2020 gas adsorption analyzer. [ 29 ] Zeolites have already been widely used in many industrial processes.…”
Section: Zeolitesmentioning
confidence: 99%
“…As a result instrument manufacturers are attempting to develop automated high throughput gas adsorption analyzing units. One notable example of which is a volumetric technique that can analyze 28 samples in parallel recently developed by Wildcat Discovery Technology Inc. [ 28 ] This apparatus has recently been demonstrated in a high throughput study of cation exchanged forms of zeolites Na-A (LTA) and Na-X (FAU) for use in CCS, with the results acquired from the high throughput analyzer validated against data acquired from a conventional Micromeritics ASAP 2020 gas adsorption analyzer. [ 29 ] Zeolites have already been widely used in many industrial processes.…”
Section: Zeolitesmentioning
confidence: 99%
“…353 K, moderate hydrogen desorption temperatures, high equilibrium pressures, 10 excellent reversibility, 11 good water saturated stability and so on. 12 A number of investigations [13][14][15][16][17][18] targeting at kinetic improvement led to a remarkable temperature drop from ca. 523 to 380 K, at which the equilibrium pressure was ca.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Considerable efforts have been paid to the catalytic modification of the system. [24][25][26][27][28][29][30][31][32][33][34][35] However, because additives have to interact with the reacting species at the interface or be accommodated in the solid phases to assist mass transport, most conventional hydrogenation catalysts, such as Ti, Co, Ni, Pd, Pt, and/or their salts, are found to have a limited effect on this system. [24,29] Recently, we found that the introduction of a small amount of KH can significantly enhance the reaction kinetics; in particular, reversible hydrogen release and uptake can be performed at a temperature as low as 107 8C.…”
Section: Introductionmentioning
confidence: 99%